Pengaruh Kemampuan Berpikir Kritis dan Kepercayaan Diri terhadap Kemampuan Pemecahan Masalah Matematika - Namira Dyah Ramadhani; Amalia Fitria (Pendidikan Matematika FKIP Universitas Mataram, 2025)
Critical thinking skills and self-confidence are two crucial elements supporting students’s academic proficiency, particularly in mathematics education. This study investigated the impact of critical thinking ability and self-confidence on the mathematical problem-solving skills of tenth-grade high school students. A quantitative, ex-post facto research design was employed. The study’s population consisted of all tenth-grade students at SMA Negeri 1 Kedungwuni, with a sample of 30 students from class X.E.7 selected via simple random sampling. Collection involved both test instruments and questionnaires. Essay questions were used in the tests to asessess critical thinking and mathematical problem-solving abilities, while the questionnaires measured student’s self-confidence levels. The tests were conducted directly, whereas the questionnaires were distributed via Google Form. Analysis techniques for this research included simple linear regression and multiple linear regression. The analysis results revealed a significant influence, both partially and simultaneously, of critical thinking skills and self-confidence on mathematical problem-solving ability. The synergy of these two factors mutually supports and enhances students’ optimal performance in solving mathematical problems.